The effects of spraying with onion and garlic extracts on the growth of the plant Anethum graveolens L. and its antioxidant effectiveness - Hamza, Rasha Kadhim; Hamed, Nadia Nasser; Al-Mazirah, Hajar Sattar (Acta Agraria Debreceniensis, 2024)
This experiment was conducted during the 2022–2023 agricultural season in a mixed clay soil at one of the fields of the Faculty of Agriculture, Basra University. The aim of the experiment was to investigate the effect of spraying dill plants (Anethum graveolens L) with aqueous extracts of onion and garlic on their growth. The plants were sprayed with garlic aqueous extract at three concentrations (0, 20, 30 g L-1) and onion aqueous extract at three concentrations (0, 15, 25 g L-1), with three applications at a 15-day interval between each spray. The experiment was designed using a Randomized Complete Block Design (RCBD).The obtained results showed that the plants sprayed with garlic aqueous extract exhibited significant improvements in most characteristics, except for the fruit content of total dissolved carbohydrates and the yield of fruits from volatile oil. Specifically, the plants sprayed with a concentration of 30 g L-1 outperformed the other two concentrations in terms of plant height (cm), number of branches per plant, and 1000-seed weight for each experimental unit. On the other hand, the plants sprayed with a concentration of 20 g L-1 significantly outperformed in terms of floral inflorescence number per plant and seed yield. Additionally, the plants sprayed with a concentration of 30 g L-1 had the highest chlorophyll content and antioxidant effectiveness of dill leaves (%). However, spraying with garlic extract did not have a significant effect on the fruit content of total dissolved carbohydrates and the yield of fruits from volatile oil.Regarding the plants sprayed with onion extract, they showed overall superiority in most traits, except for the chlorophyll content of the leaves. Specifically, the plants sprayed with a concentration of 15 g L-1 significantly excelled in plant height, while the plants sprayed with a concentration of 25 g L-1 outperformed in terms of floral inflorescence number per plant and seed yield. The plants sprayed with a concentration of 25 g L-1 also had the highest content of total dissolved carbohydrates in fruits and the highest antioxidant effectiveness of dill leaves and seeds (%). However, the plants sprayed with a concentration of 15 g L-1 had the highest yield of volatile oil. The interaction between the two factors (garlic and onion extracts) had a significant effect on all studied traits, except for the chlorophyll content of the leaves.